Three revolutions in macroeconomics: Their nature and influence - David Laidler (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2013)
Harry Johnson's 1971 ideas about the factors affecting the success of the Keynesian Revolution and the Monetarist Counter-revolution are summarised and extended to the analysis of the Rational Expectations - New Classical (RE-NC) Revolution It is then argued that, whereas Monetarism brought about a revival of the quantity theory of money from the limbo into which Keynesianism had pushed it, RE-NC modelling was responsible for that theory's most recent disappearance. This happened despite the fact that, initially, RE-NC economics appeared to be a mainly technical extension and refinement of Monetarism, rather than a radically new economic doctrine. Some implications of this story for todays' macroeconomics are briefly discussed.
Keywords: B21; E31; E41; E52; 330; Keynesianism; Monetarism; Rational expectations New Classical economics Quantity Theory; Money; Velocity; Monetary policy; Inflation; Unemployment; Business cycle; Phillips curve